Pengaruh Penyuluhan Perilaku Hidup Bersih dan Sehat (PHBS) Terhadap Pengetahuan, Sikap dan Tindakan PHBS Keluarga di Desa Lok Buntar Kecamatan Sungai Tabuk Kabupaten Banjar Kalimantan Selatan - Norhasanah Norhasanah; Rosita Rosita; Yuliana Salman; Siska Emelia (Jurnal Kesehatan Indonesia, 2017)
The purpose of this study was to analyze the influence of counseling about clean and healthy life behaviour (PHBS) to knowledge, attitude and action of PHBS family in the village of Lok Buntar Sungai Tabuk South Kalimantan. This study used a pre-eksperiment design method with One group pre test and post test design.Wilcoxon signed ranks test and Paired t test results showed an influence between counseling about Clean and Healthy Life Behaviour (PHBS) on knowledge, attitudes and action of PHBS Family. That result showed an difference of knowledge, before and after counseling. That also showed an attitude and action about PHBS.Before counseling the knowledge of respondents in good category as much 7 respondents (23%) and after counseling increased to 22 respondents (73,4%). About attitude of PHBS, before counseling in good category as much 1 respondents (3,3%) increase to 11 respondents (37%) in after counseling. About action of PHBS, before counseling nothing respondents in good category and after counseling increase to 9 respondents (30%) in good category